The expansion of varieties in the new age of advertising - Salomé Baslandze; Jeremy Greenwood; Ricardo Marto; Sara Moreira (Federal Reserve Bank of Atlanta, 2023)
The last decades have seen large improvements in digital advertising technology that allowed firms to better target specific consumer tastes. This research studies the relationship among digital advertising, the rise of varieties, and economic welfare. We develop a model of advertising and varieties where firms choose the intensity of digital ads directed at specific consumers as well as traditional ads that are undirected. The calibrated model shows that improvements in digital advertising have driven the rise in varieties over time. Empirical evidence is presented using detailed micro data on firms' products and advertising choices for the 1995-2015 period. Causal analysis using exogenous variation in consumers' differential access to the internet supports the suggested mechanism.
Keywords: E13; L15; I31; M37; O14; O31; 330; digital (directed) advertising; traditional (undirected) advertising; specialization; targeting; internet; varieties; welfare